Preparation of Biodegradable and Low-Cost Lignin-Based PVOH Carbon Fibers Prepared by Electrospinning - Amir Hamzah Siregar; Aditia Warman; Mahyuni Harahap; Grace Nainggolan; Dellyansyah Dellyansyah; Saharman Gea (Universitas Gadjah Mada, 2021)
A polyvinyl alcohol (PVOH)/lignin nanofiber was prepared by the electrospinning method as a precursor for biodegradable and low-cost carbon fibers. PVOH 15% was dissolved in water, and various concentration of lignin (5, 10, 15, 20, and 25%) was added. The presence of lignin in PVOH solution increased the viscosity and conductivity. From SEM analysis, PVOH solution produced smooth fiber, whereas the addition of lignin produced fibers in bead forms. The presence of lignin above 20% in PVOH did not produce spun-fiber. FTIR analysis confirmed that lignin was able to form hydrogen bonds with PVOH. TGA analysis showed that PVOH/lignin nanofibers had the highest residual mass, i.e., 40% at 600 °C. The morphology of the carbon fibers showed flake forms with many pores and had 58.07% carbon content.